Advanced Principles & Practices Of Agronomy - Buddhadeb Bhattacharya; Buddhadeb Bhattacharya (Ludhiana Kalyani, 2009)
Indian Agriculture has entered in to the era of globalization. various corparate bodies are launching exportable value added processed food products agro industries in all most all the states.
Crop Classification Agrometerology Manures
Keywords: Crop Classification, Agrometerology ,Manures